Analisis Evaluasi Merek AQUA Galon - Solihat Solihat; Silfi Purnama Nur; Syamsul Hidayat (PT. ALHAFI BERKAH INDONESIA, 2024)
Aqua is a brand of bottled drinking water (AMDK) produced by PT. Aqua Golden Mississippi Tbk. in Indonesia which is processed from pure mountain spring water with highly preserved mineral content using advanced filtration technology with natural purity that is highly maintained. This research aims to find out how trusted the Aqua Gallon brand is for consumption among Bina Bangsa University students majoring in accounting. This research was conducted by taking a sample of 135 respondents and tested with the help of Microsoft Excel.